Thailand’s Path to Economic Recovery and Advancement: Diagnostic Study on the Middle Income Trap and Prospects for Post-Covid Economic Growth - Benyaapikul, Pornthep (Thammasat Review of Economic and Social Policy, 2021)
For more than a decade before the Covid-19 pandemic and recession, Thailand was moving into a more advanced development phase. Unable to sustain growth based primarily on cheap labor and capital accumulation, the country needed to transform to a more knowledge- based, innovation-driven economy able to compete in the rapidly evolving global economy. Yet, structural transition to this new phase has been difficult and slow. Unfortunately, the current crisis will make this problem worse. Following an initial surge in growth as the economy recovers, the long-term problem of flattening productivity and slow growth will almost certainly reemerge to threaten future prosperity. Thailand needs to accelerate the pace of reforms essential to encourage industrial upgrading. A diverse set of challenges need to be addressed to restructure the Thai economy. This paper focuses on three reforms necessary for lowering the limits on future growth: 1) speeding up the pace of innovation, 2) removing constraints to competition, and 3) reducing inequality.